POLA DIALOG TRANSFORMATIF DALAM INJIL YOHANES 1 – 4 TERKAIT UPAYA PELAKSANAAN MISI ALLAH - Markus Simanjuntak (STT Saint Paul Bandung, 2021)
The transformative dialogue approach has an essensial role in developing the Gospel story, as seen in the Gospel of John chapters 1-4. In his Gospel, John saw dialogue as a critical element in carrying out God's mission. After conducting an investigation based on qualitative research methods with a biblical study approach in this study, it is confirmed that the transformative dialogue in the Gospel of John 1-4 serves to interpret the language through which the conversation brings meaning to the person and work of Jesus. Characters that are presented in dialogues encourage readers to take particular actions. Thus, moving the plot toward its ultimate goal